Fertility Dynamic in the Republic of Moldavia and in the European Ex-Soviet Countries: Convergences and Divergences - Gagauz, Olga; Grigoraș, Ecaterina (Calitatea Vieții, 2018)
The new aspect of fertility models assumes that postponing fertility has emerged as a determinant of differences in fertility levels in the ex-Soviet countries of the European region (Russia, Belarus, Ukraine, Moldova, Latvia, Lithuania and Estonia). The article presents the results of the research on the specific features of the fertility transition in the Republic of Moldova and the ex-Soviet countries in the European region. Based on transversal and longitudinal approach, convergence and divergence in the transformation of the fertility model were determined; the factors that determine the degree of restoration / increase of TFR for calendar years were highlighted. The results indicate that the fertility profile has changed greatly in all the analysed countries, there is a shift in age-specific fertility rates from high values and young ages to low rates and mature ages. A high degree of fertility heterogeneity at the onset of transition is determined by the different tempo of births postponement. The Baltic countries are most advanced in moving to a late fertility model, while in the Republic of Moldova, Russia, Ukraine and Belarus an earlier fertility model is maintained. The postponement of fertility started with cohorts born in the 1970s in Belarus, Russia, Latvia, Lithuania, Estonia, while in the Republic of Moldova to those born in the 1980s. The slower restructuring of the fertility profile in the Republic of Moldova is due to the prevalence of the rural population in the total population, which have a more traditional behaviour and lifestyle. The more intense recovery of postponed births in Estonia and Lithuania is due to family policies that facilitate the reconciliation of work and family life. Russia, Ukraine and Belarus, despite the promotion of birth-boosting policies, have a lower completed cohort fertility rate, which demonstrates the low efficiency of financial incentives.